Link and Match: Sinkronisasi Pembelajaran Akuntansi Vokasi dengan Karir Akuntan Era Society 5.0 - Sarah Dewiyanti; Muhammad Abdi Munsyii Julaytenth; Sinar Rohana; Hilda Octavana Siregar (Jurnal Akuntansi dan Audit Syariah)
Vocational accounting education is education that prepares students and students to become reliable accountants in the future. By prioritizing the focus of practice-based learning rather than theory, vocational accounting graduates both at the vocational and diploma level are believed to make a major contribution to the progress of the nation. However, in its implementation there are still many cases of learning in the field of accounting that do not support the needs of the world of work, especially in the era of society 5.0. This study aims to analyze the synchronization of vocational accounting learning with the needs of the workforce in the era of society 5.0 and the concept of vocational accounting learning that is in accordance with the needs of the workforce in the era of society 5.0. This research is a type of descriptive qualitative research. The subjects of this research are students majoring in accounting, while the object of this research focuses on the Special Region of Yogyakarta. The results of this study are that there is a lack of synchronization of accounting learning in several vocational schools and universities with the needs of the business world/industrial world which are increasingly leading to the era of society 5.0. The government is now increasingly concerned with vocational education with the link and match program initiated by the Director General of Vocational Education so that there is a need for a learning curriculum that is closely related to the needs of the business world/industrial world.